Dynamics of Relationship Maintenance: The Influence of Emotional Support and Trust - Ballester-Ripoll , Rafael; Corazza , Lia; Jurin , Richard; Hooshmandi, Roodi; Demetrovics , Orsolya (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The objective of this study was to investigate the roles of emotional support and trust in predicting relationship maintenance in romantic couples. Methods and Materials: A cross-sectional design was employed, involving 280 participants in committed romantic relationships. Participants completed standardized questionnaires measuring relationship maintenance, emotional support, and trust. Data were analyzed using Pearson correlation and linear regression analyses to explore the relationships between these variables. SPSS-27 software was utilized for statistical analysis, and assumptions of normality, linearity, homoscedasticity, and multicollinearity were checked and confirmed. Findings: The regression model indicated that emotional support (β = 0.46, p < 0.001) and trust (β = 0.38, p < 0.001) were significant predictors of relationship maintenance, explaining 46% of the variance (R² = 0.46, F (2, 277) = 118.36, p < 0.001). The findings underscore the critical roles of emotional support and trust in relationship maintenance. Both factors significantly contribute to sustaining romantic relationships, with emotional support showing a slightly stronger influence. Conclusion: These insights can inform relationship counseling and interventions aimed at enhancing relationship stability through targeted support and trust-building activities.